The Metaphorical Use of Language in Deuterocanonical and Cognate Literature - Behnke, Sven; Witte, Markus (Deuterocanonical and cognate literature yearbook, 2015)
Metaphors are a vital linguistic component of religious speech and serve as a cultural indicator of how groups understand themselves and the world. The essays compiled in this volume analyze the use, function, and structure of metaphors in Jewish writings from the Hellenistic-Roman period (including the works of Philo and the texts of Qumran), as well as in apocryphal early Christian texts and inscriptions.